Comparison of Energy of the Sitnikov's Restricted three Body Problem if the Primaries are Sources of Radiation, Oblate Spheroids and Triaxial Rigid Bodies - Thapa, Raju Ram (Journal of Institute of Science and Technology, 2015)
The paper establishes the energy of Stinikov's restricted three body problem when the primaries are source of radiations, oblate spheroids and triaxial rigid bodies. The effect of source of radiations, oblate spheroids and triaxial rigid bodies with their corresponding equation of motions has been studied. The equation of motions of third body is used to calculate the required energy of the infinitesimal body. Journal of Institute of Science and Technology, 2015, 20(1): 59-63